Aesthetic rehabilitation of post orthodontic treatment with lithium disilicate veneers: a case report - Halim, Davin Adijaya; Bonifacius, Setyawan; Damayanti, Lisda (Padjadjaran Journal of Dentistry, 2025)
Introduction: Treating malpositioned anterior teeth requires more than just prosthodontic intervention. A collaboration with orthodontic treatment is the preferred approach for patients with compromised cases. Due to their predictable results and tooth structure conservation, lithium disilicate veneers are indicated for the aesthetic rehabilitation of anterior teeth with malpositioning or anomalous appearance. This case report discusses the aesthetic rehabilitation of upper anterior teeth that were compromised by missing teeth and post orthodontic treatment, using lithium disilicate veneers. Case Report: A 25-year-old female patient came to the Department of Prosthodontics at Universitas Padjadjaran Dental Hospital seeking to improve her smile. The treatment history revealed that the patient had just finished her orthodontic treatment. Clinical examinations showed the absence of upper left central incisor, causing the lateral incisor to occupy the central incisor position, the canine to occupy the lateral incisor position, and the premolar to occupy the canine position. Lithium disilicate veneers were proposed and the patient consented to the treatment. A dental impression was taken, followed by a diagnostic wax-up, mock up and finally, lithium disilicate porcelain veneers were placed. Lithium disilicate was chosen due to its high aesthetic properties and minimally invasive preparation. Conclusion: Aesthetic rehabilitation of upper anterior teeth that were compromised by missing teeth and post orthodontic treatment with lithium disilicate veneers is highly technique- and material-sensitive. However, when used with proper knowledge and skill, these restorations provide excellent aesthetic and functional outcome.